171 cases of thyroidectomies: Statistical analysis - Estrugo, Roberto; Perrone, Luis; Paperán (h), Juan; Bercianos, Carlos; Gregorio, Luis; Toledo, Nancy; Iraola, María (Cirugía del Uruguay, 1976)
171 thyroidectomies were performed between 1970 and 1975 due to different pathologies and the paper presents their statistical analysis. 38 % corresponded to hyperthyroidisms. 10 % of total, ( 18 cases) were cancers, most of them differenciated, 3 medullary, 2 nondifferenciated and a secondary cancer. 6 total and 79 subtotal thyroidectomies were performed, as well as 78 more limited resections. In 9.4 % of cases postoperatory complication,s arose -mainly in surgery of hyperthyroidism- such as: 2 cases of important hemorrhages; 2 tracheolarynx obstructions; 9 cases of tetanies ( 5.2 % ) • generally definitive; and 9 recurrent laryngeal nerves lesions, 3 of which were bilateral. Death-rate was nil.